Effects of Different Types of Virtual Reality Display on Presence and Learning in a Safety Training Scenario - Buttussi, Fabio; Chittaro, Luca (IEEE transactions on visualization and computer graphics, 2018)
The increasing availability of head-mounted displays (HMDs) for home use motivates the study of the possible effects that adopting this new hardware might have on users. Moreover, while the impact of display type has been studied for different kinds of tasks, it has been scarcely explored in procedural training. Our study considered three different types of displays used by participants for training in aviation safety procedures with a serious game. The three displays were respectively representative of: (i) desktop VR (a standard desktop monitor), (ii) many setups for immersive VR used in the literature (an HMD with narrow field of view and a 3-DOF tracker), and (iii) new setups for immersive home VR (an HMD with wide field of view and 6-DOF tracker). We assessed effects on knowledge gain, and different self-reported measures (self-efficacy, engagement, presence). Unlike previous studies of display type that measured effects only immediately after the VR experience, we considered also a longer time span (2 weeks). Results indicated that the display type played a significant role in engagement and presence. The training benefits (increased knowledge and self-efficacy) were instead obtained, and maintained at two weeks, regardless of the display used. The paper discusses the implications of these results.